Royal Words in Transition: A Pragmatic Analysis of Pakubuwono XIV’s Javanese Speech Acts - Budi Purnomo (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2026)
This study examines the pragmatic construction of authority, commitment, and cultural legitimacy in the coronation address of Pakubuwono XIV delivered during the Jumenengan ceremony at the Surakarta Palace. While speech act studies have widely explored political speeches, institutional communication, and public rhetoric, contemporary royal discourse in Indonesia remains underexplored, particularly within Javanese sociocultural settings. Using a qualitative descriptive design, this study analyzes the official speech text as a form of ceremonial-institutional discourse. Data were examined through Speech Act Theory, supported by politeness theory and cultural pragmatics frameworks. The findings reveal that declarative, commissive, and directive acts dominate the address. Declarative acts function to formally enact kingship and legitimize institutional authority. Commissive acts articulate commitments to religion, palace governance, public welfare, and national loyalty. Directive acts guide palace members and the wider public through culturally mitigated forms consistent with Javanese norms of harmony and respect. Expressive acts occur less frequently and primarily communicate ethical stance rather than personal emotion. The study demonstrates that royal discourse continues to operate as a strategic communicative resource for negotiating continuity between traditional kingship and modern statehood. Theoretically, this article extends speech act scholarship into a non-Western ceremonial context. Practically, it contributes to understanding leadership communication in culturally rooted institutions undergoing sociopolitical transition.